Caregivers' views on cannabis use for their children with autism. (April 2023) - Sivori, Taylor T.; Capron, Maclain; Graves, Daniel; Harris, Jill; Schaaf, Roseann C.
Abstract: Background: Autism is a neurodevelopmental disorder impacting 1 in 44 children that is characterized by decreased social communication and problem behaviors. Despite the increasing accessibility of cannabis, there is limited guidance about its use and usefulness for autism. The purpose of this study is to query caregivers of autistic children about their experience, knowledge and interest in medical cannabis use for their children. Method: Survey methodology was used to query caregivers of autistic children between ages five to ten years. Informants recruited through a large children's hospital in New Jersey and the Autism Speaks website. Descriptive analyses of frequencies and percentages are reported and relationships among socio-demographic variables and survey responses were conducted. Results: Of the 4385 surveys sent, 568 responded. Informants were primarily white or Latino, female, and without a college education. Most were not familiar with cannabis use in autism; 7.2 % had experience providing their child with cannabis. Information about cannabis was drawn mainly from the Internet. Eighty-five percent of participants reported that they were willing to try cannabis for their child with ASD to address difficulty focusing, hyperactivity, sensory sensitivities, and anxiety. About half of those respondents were concerned about interactions between cannabis and current medications. Conclusions: Findings suggest a willingness among caregivers to use cannabis for their children with ASD, but a need for more informed guidance on this topic. More studies are needed to understand the utility of cannabis for autistic individuals; clear and reputable information about cannabis and ASD is needed. Highlights: Caregivers show interest in trying cannabis for their autistic child. Caregivers are interested in trying cannabis to address a variety of symptoms. Symptoms include difficulty focusing, hyperactivity, sensory sensitivities, anxiety. Caregivers obtain information about cannabis primarily via the Internet. Cannabis and current medication interactions may be a concern.